2017
DOI: 10.1007/s00520-017-3657-0
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured sedentary behavior and quality of life among survivors of early stage breast cancer

Abstract: Purpose This study examined relationships between sedentary behavior accumulated in different bout durations and quality of life (QoL) among breast cancer survivors. Methods Postmenopausal breast cancer survivors completed the Short Form Health Survey to assess QoL and wore an accelerometer to measure sedentary behavior and physical activity between August 2011 and May 2013. Results Participants (n=134) averaged 509.7 mins/day in sedentary time with 285.2 min/day in short bouts (<20 minutes) and 224.5 min/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…The final review contained 33 original research articles from 29 separate studies. Nine studies addressed mortality, 21-29 16 (19 publications) addressed patientreported outcomes, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 5 addressed anthropometric outcomes. [49][50][51][52][53] No studies reported data for sedentary behavior and cancer progression or recurrence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final review contained 33 original research articles from 29 separate studies. Nine studies addressed mortality, 21-29 16 (19 publications) addressed patientreported outcomes, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 5 addressed anthropometric outcomes. [49][50][51][52][53] No studies reported data for sedentary behavior and cancer progression or recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…32,34,35,37,42,43,46 One prospective study and 3 cross-sectional studies found statistically lower QoL or lower QoL subscores (physical functioning, disability, and general health) in more sedentary survivors. Two prospective studies and 5 cross-sectional studies did not identify associations between sedentary behavior and QoL.…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Moderate‐to‐vigorous physical activity (MVPA) reduces risk of cancer‐specific mortality, cancer recurrence, and chronic diseases (eg, heart disease and diabetes), while reducing fatigue and improving quality of life among cancer survivors . Furthermore, research has illustrated the deleterious effect of sedentary behavior on cancer survivors . Yet, most cancer survivors fail to regularly adhere to American Cancer Society guidelines for 150 min/wk of MVPA and spend 8‐9 h/d in sedentary activities …”
Section: Introductionmentioning
confidence: 99%